Pathologic Changes of the Peripheral Vestibular System Secondary to Chronic Otitis Media. (22nd July 2016) - da Costa Monsanto, Rafael; Erdil, Mehmet; Pauna, Henrique F.; Kwon, Geeyoun; Schachern, Patricia A.; Tsuprun, Vladimir; Paparella, Michael M.; Cureoglu, Sebahattin
Abstract : Objective: To evaluate the histopathologic changes of dark, transitional, and hair cells of the vestibular system in human temporal bones from patients with chronic otitis media. Study Design: Comparative human temporal bone study. Setting: Otopathology laboratory. Subjects and Methods: To compare the density of vestibular dark, transitional, and hair cells in temporal bones with and without chronic otitis media, we used differential interference contrast microscopy. Results: In the chronic otitis media group (as compared with the age‐matched control group), the density of type I and type II hair cells was significantly decreased in the lateral semicircular canal, saccule, and utricle ( P <. 05). The density of type I cells was also significantly decreased in the chronic otitis media group in the posterior semicircular canal ( P =. 005), but that of type II cells was not ( P =. 168). The mean number of dark cells was significantly decreased in the chronic otitis media group in the lateral semicircular canal ( P =. 014) and in the posterior semicircular canal ( P =. 002). We observed no statistically significant difference in the density of transitional cells between the 2 groups ( P >. 1). Conclusion: The findings of our study suggest that the decrease in the number of vestibular sensory cells and dark cells could be the cause of the clinical symptoms of imbalance of some patients with chronic otitis media.